Studi Kajian: Memahami Teamwork - Alfarialda, Elda Riska; Annisa, Annisa; Ahmad, Alisha; Triyana, Tamam Devi; Wardhana, Mada Aditia (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
This research analyzes scientific publication trends on teamwork (2016–2025) through a bibliometric approach. Data from 1,420 documents sourced from Scopus, Crossref, and Google Scholar are analyzed quantitatively (descriptive statistics, LDA) and qualitatively (thematic interpretation). Results indicate peak research productivity in 2018 (206 publications), followed by a significant decline until 2023, suspectedly due to the pandemic or research focus shifts. Keyword analysis identifies three dominant clusters: (1) education (